Suprasellar Hemangioblastoma on 68Ga-DOTATATE PET/CT. (11th November 2022) - Filizoglu, Nuh; Ozguven, Salih
Abstract: Von Hippel-Lindau (VHL) disease is an autosomal dominant hereditary cancer syndrome that is characterized by the presence of various malignant and benign tumors, including retinal and central nervous system hemangioblastomas. Hemangioblastomas are highly vascular tumors that can occur sporadically or within VHL disease. Herein, we present 68 Ga-DOTATATE PET/CT findings of a unique case of suprasellar hemangioblastoma in a 52-year-old man with VHL disease.